Pangan Rekayasa Genetika : Perspektif Kesehatan, Hukum Negara dan Agama - Herlina, Lenny (Lembaga Yasin AlSys, 2022)
Genetically modified food (GMO food) or in English genetically modified food which in Indonesian is popular as genetically modified food (GM food), is a biologically engineered food produced from organisms that have undergone changes that are inserted into their DNA using the method genetical manipulation. GE food is unavoidable, due to the narrowing of land and the increasingly dense population of people. Currently Worldometers notes that the world's population in 2019 reached 7.7 billion people, where the world food and agriculture organization (FAO) stated that the world must increase food production by 70% by 2050 to meet the food needs of the world community which is estimated to number 9 .1 billion at the time, meaning that fertile and very large land would be needed for agriculture to achieve this. So that GE foods, which have been initiated since 1994, must continue to be developed. This paper will focus on discussions related to legal products in the country, health and the view of Islamic law as the majority religion in Indonesia.